Rhinopharynx irrigations and mouthwash with dissolved mupirocin in treatment of MRSA throat colonization – proof-of-concept study. (January 2022) - Petersen, I.S.; Zeuthen, A.B.; Christensen, J.M.; Bartels, M.D.; Johansen, H.H.N.; Johansen, S.P.; Jarløv, J.O.; Mogensen, D.; Pedersen, J.
Summary: Background: To prevent transmission of, and infection with, meticillin-resistant Staphylococcus aureus (MRSA), eradication treatment of colonized individuals is recommended. Throat colonization is a well-known risk factor for eradication failure. Staphylococcus aureus throat colonization is associated with colonization of the rhinopharynx, but in the currently recommended Danish MRSA eradication strategies, rhinopharynx colonization is not directly targeted. Rhinopharynx colonization could therefore be an important risk factor for prolonged MRSA throat carriage. Aim: To determine whether irrigation and wash of the rhinopharynx and mouth with dissolved mupirocin is a feasible and potentially efficacious supplementary strategy against treatment-resistant MRSA throat carriage. Methods: The patient study was an open, non-blinded, trial including 20 treatment-resistant MRSA throat carriers. In the study, the patients received a supplementary treatment besides the standard treatment according to the Danish MRSA eradication strategy. The supplementary treatment consisted of rhinopharyngeal irrigation and mouth-gurgling twice a day for 14 days with a mupirocin ointment (22 g 2% ointment per litre of isotonic sterile saline solution) in a 37°C solution. Findings: Eighteen patients (90%) complied with the treatment protocol and none ex-perienced any major adverse events. Out of the 18 patients who finished the study per protocol, 15 (83%) and seven (39%) patients had negative MRSA sampling results one and six months after end of treatment, respectively. Conclusion: This study demonstrates the feasibility and clinical potential of also targeting the rhinopharynx and oropharynx in non-systemic throat MRSA eradication strategies.